Fungos Conidiais Sapróbios na Serra da Fumaça, Pindobaçu, Bahia - Almeida, Davi Augusto Carneiro de (2010)
The conidial fungi are a polyphiletic group of assexual fungi that have the sexual stages in Ascomycota and Basidiomycota. This group has two primary functions into ecosystems: recycling activity of nutrients through the decomposer and interference in primary production through symbiosis with plants. This research shows the results of a taxonomic study of conidial fungi associated with leaf litter and submerged dead plant material, in Serra da Fumaça, municipality of Pindobaçu, state Bahia. Three expeditions to Serra da Fumaça, from August to December 2008 were made. Samples of leaf litter were collected in two vegetational types: campo rupestre and mata ciliar. Submerged dead plant materials were collect only in Mata Ciliar. All samples were transported to the Mycology Laboratory at the Universidade Estadual de Feira de Santana. The samples were washed in water and then incubated in moist chambers at room temperature for 30 days. Slides were prepared and deposited in the Herbarium HUEFS. Fifty-six species of conidial fungi were identified, including 55 hyphomycetes and one agonomycetes. The results are presented in three chapters. The first one shows 49 species identified, eigth of them are new records for the Neotropics, three to South America and two for Brazil. The second one treats on the taxonomic study of five new species with some notes on the genus Janetia and a key to Anungitopsis species. The last one is dedicated to propose two new genera of conidial fungi.